Efektivitas Pemberian Vaksin terhadap Keterpaparan Covid-19 Tenaga Kesehatan di Kantor Kesehatan Pelabuhan Kelas I Soekarno Hatta - Budi Hendrawan; Yeny Sulistyowati; Sri Utami; Jontari Jontari (JURNAL BIDANG ILMU KESEHATAN, 2023)
Indonesia continues to launch vaccination programs to achieve herd immunity. For now, the Pfizer and Moderna vaccines complement the line of COVID-19 booster vaccines used by Indonesia. The government decided on the need to protect health workers as health workers who must be guaranteed their health in order to continue to provide health services to the community by issuing circulars and technical guidelines for the implementation of Bosster vaccinations for health workers, health worker assistants and other supporting personnel using the Moderna vaccine. This study was conducted to determine the effectiveness of vaccination with COVID-19 exposure of health workers at the Soekarno Hatta Health Office Class I Port. By using analytical observational research with a crossectional design. The sample in this study were 129 respondents. The research analysis used univariate, bivariate (paired sample t-test) and multivariate (logistic regression). Then it was found that there was a difference in the effectiveness of giving doses 1 and 2 of COVID-19 vaccination (Sinovac) with COVID-19 exposure. There is a difference in the effectiveness of giving doses of COVID-19 vaccination 1, 2 and dose 3 (Booster) with COVID-19 exposure and there is a significant difference between giving doses of COVID-19 vaccination 1 and 2 (Sinovac) and giving doses of COVID-19 vaccination 1, 2 and dose 3 (Booster) to the COVID-19 exposure of health workers at KKP Class I Soekarno-Hatta. And the most dominant factor is the administration of doses 1, 2 and 3 (Booster) vaccinations. Therefore, it is hoped that the Soekarno Hatta Class I KKP can provide Lab-based COVID-19 Serology Tests. Keywords: Vaccination, booster and exposure to COVID-19